EFFECT OF AEROBIC TRAINING PROGRAM ON STRENGTH AND BONE MINERAL DENSITY OF OVARIECTOMIZED RATS (Fiep Bulletin - online, 2011)
Introduction: Hypoestrogenism or abstinence of estrogen causes rapid bone loss faster installation of osteoporosis. Moreover,exercise represent an important factor in preventing osteoporosis,since it consists of mechanical stimulation induces remodeling and osteogenesis. Objectives: To compare the effects of aerobic exercise protocol and strength exercise on osteopenia in ovariectomized rats. Methods: Adults rats (250 to 300g) divided into three groups (8/group): control (G1) - oophorectomy; G2-oophorectomy + swimming, G3-oophorectomy + strength exercise. The training started 40 days after ovariectomy and a week of adaptation to the aquatic environment. G1 had its activities restricted to the cage. At the end of the trial determined the serum levels of calcium, phosphorus, alkaline phosphatase, creatinine, total protein and albumin. The left femur was weighed and determined the radiographic bone density. Results: G1 showed higher body mass and increased weight gain after the trial period. Phosphorus concentrations and alkaline phosphatase were higher in G2 (4.97 ± 0.47, 75.04 ± 7.66) and G3 (4.95 ± 0.33, 69.13 ± 6.47) compared with G1 (7.06 ± 0.36, 37.14 ± 2.94) and creatinine was higher in G3 (0.63 ± 0.035 p
Keywords: ovariectomy; osteoporosis; physical activity